THE EFFECTIVENESS OF INTRAFERTIL IN GYNECOLOGICAL PRACTICE AND ITS ROLE IN RESTORING REPRODUCTIVE HEALTH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This scientific article examines the clinical effectiveness of Intrafertil in gynecological practice, focusing on its role in optimizing the intrauterine environment, regenerating the endometrium, reducing inflammatory processes, and improving fertility outcomes. The study assessed endometrial thickness, follicular growth, and pregnancy rates in women of reproductive age before and after treatment. The obtained data demonstrated a significant positive impact of Intrafertil on endometrial regeneration and overall reproductive health restoration.